The connection between ma`ani nahwi in Arabic and modistae in Latin: An approach to the History of Linguistic studies - Yaacob, Solehah@Nik Najah Fadilah (2008)

(untitled)
The research emphasizes on the connection between the Arabic concept of maÑani nahwi and modistae in Latin. In order to identify this connection, the researcher has to elaborate on the role of Aristotle’s categories in influencing the concept of modistae in the Middle Ages first. The paper will then reevaluate the influence of Muslim philosophers such as al-Farabi (c.870-c.950 AD), Avicenna (980-1037 AD) and Averoes (c.1126-c.1198 AD) in Latin and clarify the role of Jurjani (d.1078 AD) in introducing his concept of nazm towards ma`ani nahwi. The result of the research will also enhance the understanding of the relationship between syntax and semantic which has not been effectively clarified within the framework of traditional Arabic grammatical theory.